Opto-RhoGEFs, an optimized optogenetic toolbox to reversibly control Rho GTPase activity on a global to subcellular scale, enabling precise control over vascular endothelial barrier strength - Eike K Mahlandt; Sebastián Palacios Martínez; Janine JG Arts; Simon Tol; Jaap D van Buul; Joachim Goedhart (eLife, 2023)
The inner layer of blood vessels consists of endothelial cells, which form the physical barrier between blood and tissue. This vascular barrier is tightly regulated and is defined by cell-cell contacts through adherens and tight junctions. To investigate the signaling that regulates vascular barrier strength, we focused on Rho GTPases, regulators of the actin cytoskeleton and known to control junction integrity. To manipulate Rho GTPase signaling in a temporal and spatial manner we applied optogenetics. Guanine-nucleotide exchange factor (GEF) domains from ITSN1, TIAM1, and p63RhoGEF, activating Cdc42, Rac, and Rho, respectively, were integrated into the optogenetic recruitment tool improved light-induced dimer (iLID). This tool allows for Rho GTPase activation at the subcellular level in a reversible and non-invasive manner by recruiting a GEF to a specific area at the plasma membrane, The membrane tag of iLID was optimized and a HaloTag was applied to gain more flexibility for multiplex imaging. The resulting optogenetically recruitable RhoGEFs (Opto-RhoGEFs) were tested in an endothelial cell monolayer and demonstrated precise temporal control of vascular barrier strength by a cell-cell overlap-dependent, VE-cadherin-independent, mechanism. Furthermore, Opto-RhoGEFs enabled precise optogenetic control in endothelial cells over morphological features such as cell size, cell roundness, local extension, and cell contraction. In conclusion, we have optimized and applied the optogenetic iLID GEF recruitment tool, that is Opto-RhoGEFs, to study the role of Rho GTPases in the vascular barrier of the endothelium and found that membrane protrusions at the junction region can rapidly increase barrier integrity independent of VE-cadherin.